ANALISIS POTENSI NILAI TAMBAH PENGELOLAAN LIMBAH PABRIK SAGU CV MAKMUR TIMIKA - Hero Fransiskus Lie; Zulaiha Busran, Habel Taime (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the Analysis of Potential Added Value of Waste Management of CV Makmur Timika's Sago Factory. The research method used in this research is exploratory method. Data collection techniques carried out by observation, interviews, and documentation. The analytical instrument used is the analysis of the cost of production. The results of this study indicate that the cost of production for briquettes is IDR. 10,654/kg and an added value of IDR. 267,200, while the cost of production for animal feed is IDR. 13,915/kg and an added value of IDR. 54,250